Complete Dosage Compensation in Anopheles stephensi and the Evolution of Sex-Biased Genes in Mosquitoes - Jiang, Xiaofang (Genome Biol Evol, 2015)
Complete dosage compensation refers to hyperexpression of the entire X or Z chromosome in organisms with heterogametic sex chromosomes (XY male or ZW female) in order to compensate for having only one copy of the X or Z chromosome. Recent analyses suggest that complete dosage compensation, as in Drosophila melanogaster, may not be the norm. There has been no systematic study focusing on dosage compensation in mosquitoes. However, analysis of dosage compensation in Anopheles mosquitoes provides opportunities for evolutionary insights, as the X chromosome of Anopheles and that of its Dipteran relative, D. melanogaster formed independently from the same ancestral chromosome. Furthermore, Culicinae mosquitoes, including the Aedes genus, have homomorphic sex-determining chromosomes, negating the need for dosage compensation. Thus, Culicinae genes provide a rare phylogenetic context to investigate dosage compensation in Anopheles mosquitoes. Here, we performed RNA-seq analysis of male and female samples of the Asian malaria mosquito Anopheles stephensi and the yellow fever mosquito Aedes aegypti. Autosomal and X-linked genes in An. stephensi showed very similar levels of expression in both males and females, indicating complete dosage compensation. The uniformity of average expression levels of autosomal and X-linked genes remained when An. stephensi gene expression was normalized by that of their Ae. aegypti orthologs, strengthening the finding of complete dosage compensation in Anopheles. In addition, we comparatively analyzed the differentially expressed genes between adult males and adult females in both species, investigated sex-biased gene chromosomal distribution patterns in An. stephensi and provided three examples where gene duplications may have enabled the acquisition of sex-specific expression during mosquito evolution.